Surgical Treatment of Penetrating Carotid Artery Injury - Tae Hwa Hong (Journal of Acute Care Surgery)
Penetrating carotid artery injury (PCAI) is a life-threatening condition that requires prompt diagnosis and intervention. Surgical treatment is often necessary to control bleeding, prevent complications, and restore blood flow to the brain. The choice of surgical technique depends on the severity of the injury, the patient’s overall condition, and the surgeon’s expertise. Common surgical approaches for PCAI include arterial repair, ligation, and bypass grafting. The choice of surgical approach should be based on a careful assessment of the patient’s condition and the extent of the arterial damage. Preoperative planning and intraoperative monitoring are essential to minimize complications and optimize patient outcomes. In recent years, endovascular techniques, such as angioplasty and stenting, have been increasingly used in the management of PCAI. These techniques may be considered in selected cases, especially when the injury is located in the distal carotid artery or when the patient is at high risk for surgical complications. However, the long-term durability of endovascular interventions for PCAI remains uncertain, and surgical repair may still be preferred in many cases. The choice of surgical technique should be tailored to the individual patient’s needs, and careful preoperative planning, intraoperative monitoring, and postoperative care are essential for optimizing patient outcomes.